Activity of AMP deaminase and 5′-nucleotidase in the cytosolic kidney fraction of rats under the conditions of different protein and sucrose - Voloshchuk, Oksana; Boichuk, Andriana (My University, 2022)
The goal of this work was to evaluate the activity of AMP deaminase and 5-nucleotidase in the cytosolic kidney fraction of rats under the conditions of different protein and sucrose content in a diet. The excessive consumption of sucrose against the background of alimentary protein deficiency is accompanied by an increase in AMP-deaminase and 5-nucleotidase activity in the cytosolic fraction of rat kidneys, which can be considered as a compensatory mechanism aimed at switching metabolic transformations in conditions of nutritional imbalance.
Keywords: AMP desaminase, 5-nucleotidase, kidney, low-protein diet, high-sucrose diet.